2013
DOI: 10.1037/a0032480
|View full text |Cite
|
Sign up to set email alerts
|

Group membership and social identity in addiction recovery.

Abstract: Despite a growing interest in how group membership can positively impact health, little research has addressed directly the role social identity processes can have on recovery from addiction. Drawing on social identity theory and self-categorization theory, the present study investigated how recovery group membership can introduce a new social identity associated with recovery, compared to the social identity associated with addiction. We hypothesized that two processes--evaluative differentiation and identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
180
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(201 citation statements)
references
References 36 publications
17
180
0
4
Order By: Relevance
“…SIMOR is also consistent with evidence reported by Buckingham, Frings and Albery (2013) that both substance users and smokers are more likely to remain abstinent if they identify strongly with a recovery group. In other words, as former users come to identify more strongly with recovery-oriented groups, and less strongly with using groups, their likelihood of sustained recovery increases.…”
Section: Insert Figure 1 About Heresupporting
confidence: 79%
See 1 more Smart Citation
“…SIMOR is also consistent with evidence reported by Buckingham, Frings and Albery (2013) that both substance users and smokers are more likely to remain abstinent if they identify strongly with a recovery group. In other words, as former users come to identify more strongly with recovery-oriented groups, and less strongly with using groups, their likelihood of sustained recovery increases.…”
Section: Insert Figure 1 About Heresupporting
confidence: 79%
“…As the individual cultivates their recovery-based social identity through immersion in AA activities and internalisation of AA values, so the social identity associated with their using group is diminished (Buckingham et al, 2013).…”
Section: Simor As a Basis For Understanding Aa Efficacymentioning
confidence: 99%
“…The process of social identity formation within recovery groups may help maintain cessation of the addictive substance, alluded to in the social identity model of cessation maintenance (SIMCM; Frings & Albery, 2015;Frings, Collins, Long, Pinto, & Albery, 2016, and the SIMOR model; Best et al, 2016). Here, it is suggested that when individuals are in recovery, moving from a social identity of 'addict' to one associated with recovery such as 'recovering addicts' or 'alcohol abstainers', enhances ones belief of cessation self-efficacy and control (Buckingham, Frings, & Albery, 2013). Furthermore, by identifying with others recovering (e.g., selfhelp group), individuals may feel more protected from 'falling off the wagon' as the group acts as a support (Frings et al, 2016).…”
Section: Social Drinkingmentioning
confidence: 99%
“…For example, in a study with former substance users, Buckingham, Frings, and Albery (2013) Dingle, Stark, Cruwys, and Best (2014) expanded upon these ideas by suggesting that relinquishing an addict identity would allow individuals to identify with a 'recovery identity'. They found that amongst those recovering from drug and/or alcohol abuse, treatment outcomes and wellbeing were influenced by identification with the therapeutic community (TC).…”
Section: <Figure 51 Here>mentioning
confidence: 99%